The Effect Of Discipline, Motivation And Work Environment On Employee Job Satisfaction - Ramadhani, Novia; Hadiyatno, Didik; Cipto, Rahajeng C Putri (Riwayat: Educational Journal of History and Humanities, 2025)
The aim of this research is to determine the influence of work discipline, motivation, and work environment on the employees of PT. Energy Logistic Balikpapan. This research was conducted at PT. Energy Logistic Balikpapan, with 60 respondents, using quantitative research methods. Data collection was carried out through observation and questionnaires. The data analysis technique used was multiple linear regression with the Partial Least Square (PLS) program. The research results indicate that the variables of work discipline, motivation, and work environment have a significant positive influence on employee job satisfaction at PT. Energy Logistic Balikpapan.